Role of elevation feedbacks and ice sheet–climate interactions on future Greenland ice sheet melt - T. Feenstra; M. Vizcaino; B. Wouters; M. Petrini; M. Petrini; R. Sellevold; K. Thayer-Calder (The Cryosphere)
The Greenland ice sheet (GrIS) stores freshwater equal to more than 7 m of potential sea level rise (SLR) and strongly interacts with the Arctic, North Atlantic and global climate. Over the last few decades, the ice sheet has been losing mass at a rate that is projected to increase. Interactions between the GrIS and the climate have the potential to amplify or reduce GrIS mass balance responses to ongoing and projected warming. Here, we investigate the impact of ice sheet–climate interactions on the climate and mass balance of the GrIS using the Community Ice Sheet Model version 2 (CISM2) coupled with the Community Earth System Model version 2 (CESM2). To this end, we compare two idealized multi-century simulations with a non-evolving and evolving ice sheet topography in which we apply an annual 1 % increase in CO2 concentrations, starting from pre-industrial (PI) until stabilization at 4×PI CO2 concentrations (4×CO2). By comparing the one- and two-way coupled simulations, we find significant changes in atmospheric blocking, precipitation and cloud formation over Greenland as the GrIS topography evolves, acting as negative feedbacks on mass loss. We also attribute part of the overestimation of mass loss in the one-way coupled simulation to an overestimation of melt in the ablation area caused by the use of a uniform temperature lapse rate to reflect the elevation differences between the atmospheric and ice sheet grids. Furthermore, we investigate ice sheet–climate interactions in a simulation branched in year 350 from our two-way coupled simulation in which we annually reduce atmospheric CO2 by 5 % until PI concentrations are reached. During the 350-year 4×CO2 forcing period, the ice sheet loses a total mass of 1.1 m sea level equivalent, and part of its margins retreat landward. When the PI CO2 concentration is restored, melt decreases rapidly, leading to a small positive surface mass balance. Combined with the strongly reduced ice discharge resulting from the widespread retreat of the ice sheet margin, this halts GrIS mass loss despite a remaining global warming of 2 K. The GrIS, Arctic and North Atlantic strongly interact, causing a complex transitional phase towards a colder climate during the century following the CO2 reduction. Elevated atmospheric temperatures, larger ocean heat transport and deteriorated state of the snowpack, compared to the initial pre-industrial state, result in limited regrowth of the ice sheet under reintroduced PI CO2 conditions.